Fluctuating sensoneural hearing loss as a manifestation of endolymphatic hydrops of the labyrinth - Pochuieva, Tetiana; Borysenko, Oleg; Srebniak, Ilona; Ohnivenko, Olena (Bucharest : Balkan Medical Union, 2025)
Sudden sensorineural hearing loss (SSHL) is a leading problem in modern audiology. In some cases, it becomes a low-frequency fluctuating sensorineural hearing loss (LFFSHL), which can further disturb the vestibulocochlear analyzer if the cause is not clarified and without proper treatment at its onset.
When LFFSHL is determined on audiogram, the following diagnostic approach is recommended: CT scan of the temporal bones (to rule out possible anatomical causes of hearing loss, including vestibular aqueduct widening, high location of the jugular bulb, congenital or post-traumatic perilymphatic fistula, superior semicircular canal dehiscence, and others); electrocochleography with a detailed vestibulometric study; 1.5T MRI (if possible 3T) of the temporal bones with contrast (if signs of endolymphatic hydrops are detected with an increase in the SP/AP ratio of more than 0.42 during electrocochleography). MRI with contrast assesses the degree of endolymphatic hydrops of the ipsilateral ear and the possible involvement of the contralateral ear.
Keywords: MEDICINE::Surgery::Otorhinolaryngology; MEDICINE::Surgery::Surgical research::Otoneurology; MEDICINE::Physiology and pharmacology::Physiology; fluctuating sensorineural low-frequency hearing loss; endolymphatic hydrops; electrocochleography; inner ear tomography